A History of Force Feeding Hunger Strikes, Prisons and Medical Ethics, 1909–1974 - Miller, Ian (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
This book is the first monograph-length study of the force-feeding of hunger strikers in English, Irish and Northern Irish prisons. It examines ethical debates that arose throughout the twentieth century when governments authorised the force-feeding of imprisoned suffragettes, Irish republicans and convict prisoners. It also explores the fraught role of prison doctors called upon to perform the procedure. Since the Home Office first authorised force-feeding in 1909, a number of questions have been raised about the procedure. Is force-feeding safe? Can it kill? Are doctors who feed prisoners against their will abandoning the medical ethical norms of their profession? And do state bodies use prison doctors to help tackle political dissidence at times of political crisis? This book is Open Access under a CC BY license.